2012
DOI: 10.1186/1471-2229-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping in sunflower for sclerotinia head rot resistance

Abstract: Background: Sclerotinia Head Rot (SHR) is one of the most damaging diseases of sunflower in Europe, Argentina, and USA, causing average yield reductions of 10 to 20 %, but leading to total production loss under favorable environmental conditions for the pathogen. Association Mapping (AM) is a promising choice for Quantitative Trait Locus (QTL) mapping, as it detects relationships between phenotypic variation and gene polymorphisms in existing germplasm without development of mapping populations. This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…As opposed to biparental mapping techniques, these studies are not limited by the genetic diversity restricted within two individual canola plants and therefore represent a more comprehensive way of identifying QTLs for SSR resistance in B. napus. Genome-wide association studies (GWAS) have been performed for resistance to SSR in soybean (Bastien et al, 2014) and sunflower (Fusari et al, 2012), as well as pod shatter resistance in canola (Raman et al, 2014). The recently developed B. napus GWAS ERANET-ASSYST population could be used for future SSR resistance studies (Schiessl et al, 2014).…”
Section: Genetic Resistancementioning
confidence: 99%
“…As opposed to biparental mapping techniques, these studies are not limited by the genetic diversity restricted within two individual canola plants and therefore represent a more comprehensive way of identifying QTLs for SSR resistance in B. napus. Genome-wide association studies (GWAS) have been performed for resistance to SSR in soybean (Bastien et al, 2014) and sunflower (Fusari et al, 2012), as well as pod shatter resistance in canola (Raman et al, 2014). The recently developed B. napus GWAS ERANET-ASSYST population could be used for future SSR resistance studies (Schiessl et al, 2014).…”
Section: Genetic Resistancementioning
confidence: 99%
“…Association mapping (AM) is a relatively recent quantitative trait loci (QTL) mapping approach, that has the potential for resolution to the level of individual genes (alleles) [ 8 ]. In contrast to classical QTL mapping techniques used in the analysis of complex traits, AM is a method that detects relationships between phenotypic variation and gene polymorphisms in existing germplasm collections, without development of mapping populations [ 9 , 10 ]. Until now, only four AM studies have been reported for sunflower.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only four AM studies have been reported for sunflower. The first one was conducted by Fusari et al [ 9 ] using a set of inbred lines from the breeding program of the National Institute of Agricultural Technology (INTA, Argentina), whereas the remaining three were based on germplasm collections from the USDA North Central Regional Plant Introduction Station (NCRPIS), the French National Institute for Agricultural Research, INRA and the USDA-ARS, Northern Crop Science Laboratory [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of environmental cues on flowering time is well documented in the model plant Arabidopsis thaliana where a study (Li et al, 2010) identified SNPs that can explain up to 45% of the phenotypic variation of flowering time in a large panel of natural accessions. In sunflower, GWAS are more recent: Fusari et al (2012) on disease resistance, and Nambeesan et al (2015) on branching performed their GWAS with data collected on inbred lines, whereas Cadic et al (2013) studied the genetic control of FT in a panel evaluated in 15 environments as hybrids.…”
Section: Introductionmentioning
confidence: 99%